Adnexal carcinomas of the head and neck - Guerrissi Jorge; Quiroga Juan (Indian Journal of Plastic Surgery, 2008)
Adnexal carcinomas of the skin are rare and they derive from structures such as sweat glands, sebaceous glands, and hair follicles. Adnexal tumors represent 1-2% of skin cancers. Between 1998 and 2004, eight patients with malignant adnexal tumors of the head and neck were treated in the Plastic Surgery Service in Argerich Hospital in Buenos Aires, Argentina. Four (50%) of them had malignant cylindromas, two (25%) had sebaceous carcinoma, and the other two (25%) syringoid eccrine carcinoma. Tumor resection and local flaps were made in all cases. In one case, a radical neck dissection with superficial parotidectomy was performed to treat the metastatic cervical nodes. Local recurrence observed in two cases (25%) was associated with distant metastasis and death of the patients. In other six cases, the survival rate was 75% after five years.